PENENTUAN JUMLAH OPERATOR BAGIAN PACKING DENGAN MENGGUNAKAN METODE ANTRIAN GUNA MENGURANGAI WAKTU TUNGGU DAN BIAYA - Ayudina Puji E, Teguh Baroto, (Jurnal Teknik Industri, 2000)
The  queue  in  packing   division  PT.  Domusindo  Perdana caused  of product arriving  that will  be packed over  than  service  facilities available so that long  queuing happened and  it  makes long waiting time that will  be caused  to high totally cost.Alocation  of operator number  in packing  division  that have  lot  of queue  is in Centre of Panel (1 person),  Base Assembly  (1  person),  Drawer Side, Back,  Base (1  person)  and strawpack (4 persons) after  analysis of queuing.  Using  searching analysis  of optimum  working number,   will increase  operator in  Centre Panel  Devision (3 person),  Base  Assembly (3 persons), Drawer Side, Back, Base (4 persons) and strapack (5 person) to make these  divisions don't have any queue.The increasing of service  facilities in packing  division from the initial  condition 7 persons I operator and in end  condition about  15  operators.    Overall  cost  spent   everyday decrease about Rp.   117.471.214,   00  than   the   initial   condition  Rp.   245.675.136,   00  and  the   last   condition Rp.  67.193.922  with  overall  waiting time in packing division   decrease about  25.20 minutes  than the initial  condition about   39.6 minutes to 14.4 minutes ..